Research on the gas migration trend and mechanism of the transition flow regime in coal based on MRT-LBM simulation - Liu, Yanwei; Jia, Haojie; Han, Hongkai; Zuo, Weiqin; Shi, Jin; Chang, Ping; Miao, Jian; He, Yanyan; Peng, Jie (Frontiers in Earth Science, 2022)
Gas migration within the micro/nanopores of deep low-permeability coal seams in the middle and late stages of extraction occurs in the transition flow regime, which has been a challenging and popular issue in recent years. Based on the previous establishment of a nanoporous gas transmission model considering the microboundary constraint effect and porous anodic alumina membrane experiments, numerical simulation and an experimental verification method are used to study the coal seam gas transition flow regime, accounting for the defects and limitations of the theoretical model and experimental research, to reveal the process and mechanism of gas flow in a low-permeability coal seam. First, based on Langmuir monolayer adsorption theory, the multiple-relaxation-time lattice Boltzmann method (MRT-LBM) model of gas migration in coal micro/nanopores with the slip boundary scheme and Bosanquet effective viscosity was applied. The software MATLAB was used to carry out the simulation study of uniform pore gas flow based on the MRT-LBM model, and the results were compared and verified with the laboratory experimental results. On this basis, the gas flow in coal pores with different micro/nanopore sizes considering adsorption was simulated. The results show that the dimensionless permeability coefficient increases with decreasing pore size under the same pressure, which reflects the subsequent enhancement of the microboundary constraint effect and reveals that the pore system becomes the main controlling factor of coal seam permeability within the coal matrix in the middle and late stages of coal seam gas extraction, while the role of the microboundary constraint effect needs to be considered. The gas adsorption layer weakens the pore gas flow capacity, but for pores with a radius greater than 16 nm, the apparent change in permeability caused by the adsorption layer is less than 5%, and the adsorption effect can be ignored. N2, CH4 and CO2 enter the transition flow regime under different pressure conditions; with gas extraction, the gas pressure decreases, and the difference in the gas flow characteristics of the three gases increases.